Transnational Forest Governance Arrangements dataset (TFGA-dataset) - Fredy David Polo-Villanueva; Ana Alice de Oliveira Tavares; Lukas Giessen; Sarah Lilian Burns (Annals of Forest Science)
Abstract Key message The Transnational Forest Governance Arrangements dataset is the first to compile a comprehensive set of governance arrangements whose spatial ambits span three or more national jurisdictions, and which formally address forests as a main issue. As this dataset provides information on key institutional variables of these arrangements for the year 2023, it can be reused to assess the theoretical argument that regional governance arrangements are more effective than their global counterparts, as well as to explore the drivers of institutional fragmentation in transnational forest governance. The complete dataset is available at https://zenodo.org/records/14831667 . The metadata describing the data-set is available at:  https://metadata-afs.nancy.inra.fr/geonetwork/srv/fre/catalog.search#/metadata/42c6ab18-14e8-4bd7-9669-991896c1e467 .